Red Eu, Yb:KY(WO4)2 laser at ~702 nm. (8th July 2015) - Dashkevich, V I; Bagayev, S N; Orlovich, V A; Bui, A A; Loiko, P A; Yumashev, K V; Yasukevich, A S; Kuleshov, N V; Vatnik, S M; Pavlyuk, A A
Abstract: In this letter, laser operation is demonstrated with a Eu, Yb: KY(WO4 )2 crystal on the 5 D0   →   7 F4 transition of the Eu 3+ ion. When pumping into the 7 F1   →   5 D1 absorption band by a diode-pumped Nd 3+ :KGd(WO4 )2 /KTP laser power-scaled at 533.6 nm up to a watt-level, we achieved 2.5 mW of the continuous wave (CW) red output at ~702.1 nm. At quasi-CW pumping with a duty cycle of 10%, the peak power of the ms-long pulses arrived at ~19 mW, corresponding to a green-to-red conversion efficiency of 0.8%.